The Effectiveness of Health Communication in Preventing Stunting - Ridho, Fiki Muhammad; Fauzan, Moh.; Faisal, Ahmad; Hanafi, Hanafi (Penerbit Goodwood, 2023)
Purpose: Stunting is a chronic nutritional problem that remains a primary concern in Indonesia; it requires considerable attention and is one of the Sustainable Development Goals (SGDs). Stunting prevention is very important, and one program that can be implemented is health communication. This study aimed to evaluate, review, and criticize published articles regarding the effectiveness of health communication in efforts to prevent stunting. Methodology: A systematic and comprehensive literature search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using the following databases: PubMed, ScienceDirect, and Google Scholar until September 2023. Results: All the included studies stated that health communication has a significant positive impact on stunting prevention through three types of communication: interpersonal, group, and mass communication. The messages conveyed by communicators to communicants cover most of the important messages that must be conveyed, including exclusive breastfeeding, complementary foods, BMI and HAZ scores, and nutritional behavior. The methods used also varied, ranging from counseling methods at posyandu or integrated healthcare centers, use of flipcharts, radio, TV, support groups, home visits, mobile outreach, food production, and training of community health workers. Limitations: According to the review, this study has limitations, including a limited number of studies, and the research population is not spread across every region in the world; consequently, the results of this review may not be able to represent all populations and races globally. Contribution: We hope that the findings of this study can be used as a reference for further research related to stunting management using a health communication approach. In addition, this study can be used as a reference source for conducting outreach, interpersonal communication, group communication, and mass communication related to stunting, so that stunting prevention programs in Indonesia can be implemented widely and comprehensively.